Turning a blind eye to dying and eroticism: some remarks on contemporary cinema - Jakubowska, Małgorzata; Michałowska, Monika (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Since the beginning of the cinematographic industry there has been a visible interest in exploring two themes: death and sex, whereas the motif of dying and sexuality/eroticism seem to be mutually exclusive in mainstream movies to such extent that they rarely appear together on the screen. To shed some light on this cinema tendency of separating eroticism from dying we investigate some of the factors of the phenomenon as well as the ones that could have contributed to the shift we have noticed. The majority of films devoted to the subject of dying and eroticism concentrate on a very limited range of visual and narrative schemes. In our paper we present the main clichés, plot and visual schemes, motifs and narrative techniques in contemporary cinema. Although the unique power of the cinema is “matter of making images seen”, it could be argued that the cinema uses not only the command ‘open your eyes to’, but also the command ‘close your eyes to’. In this way, audiovisual culture closes its eye to the entwinement of the motif of dying with the themes of eroticism.